THE ASPECTS OF QUALITY MANAGEMENT IN CONTINIOUS PROFESSIONAL TRAINING OF TEACHERS - ANDRIȚCHI, Viorica (Acta et Commentationes, Sciences of Education, 2019)
This article addresses the problem of the quality for professional forming of teachers. As a result of the comparative analysis and experimental studies, it was deduced the criteria of the quality for professional forming; thus there are highlighted the principles for confirming the quality training of teachers and also it was proposed a series of actions for implementing appropriate the system of management quality in institutions of professional forming.